Dynamic simulation of coupled transmission processes and reaction mechanisms in porous calcined limestone. (9th January 2017) - Li, Mingchun; Yang, Hao; Song, Lanting; Wu, Yusheng; Liang, Jiyan
Abstract : The particle reaction model and dynamic reaction characteristics of limestone over a wide particle size range from 0.15 to 10 mm were studied by thermogravimetric analysis and nitrogen adsorption‐desorption techniques. A clear boundary between the sintered porous product layer and the undecomposed part was found by field emission scanning electron microscopy (FESEM) analysis. A dynamic coupling model considering the effects of varied pore structure and transport resistances was established based on the appropriate particle reaction model, which allowed us to predict the decomposition ratio and reaction regimes in a broad range of particle sizes. The dynamic characteristics of pore size distribution and reaction mechanisms were discussed. Over the defined particle size range and calcination temperature range, the diffusion of gaseous product through porous product layer will become the rate determining factor as the ratio of ( r 0 ‐ r c )/ r 0 corresponding to 25 % Damköhler number above 0.35.